Combining conventional and volunteered geographic information to identify and model forest recreational resources. (June 2015) - Upton, Vincent; Ryan, Mary; O'Donoghue, Cathal; Dhubhain, Aine Ni
Abstract: It is now common for researchers in natural resource management and economics to develop spatial models of recreation demand for the purposes of valuation and planning. Such an approach has significant advantages but requires access to relatively detailed spatial data. In the absence of official data concerning resources, researchers may benefit from employing increasingly available volunteered geographic information (VGI) as a central source of data or to complement more traditional data sources. This paper describes the development of a map of forest recreational resources in Ireland by combining conventional forest cover data and VGI of recreational trails. As an extension the new map is combined with household survey data to explore respondent's ability to identify local recreational forests and models the impact of the characteristics of the closest forest on their annual visitation. The results suggest that VGI can be a useful resource to researchers in both the identification and characterisation of recreational resources. In addition, this paper finds that the distance to and characteristics of the nearest recreational forest has a significant impact on total annual visitation by members of the public. Highlights: Volunteered Geographic Information (VGI) is increasing in availability and spread. VGI from OpenStreetMap was employed to identify and characterise recreation forests. The resulting map of recreation forests in Ireland can be used in research and planning. These data can also generate meaningful variables for recreational demand modelling. Significant potential exists for researchers to employ VGI more extensively.